The Right of Access to Health Care for Migrants in the Republic of North Macedonia - Barriers and Challenges - Jankulovska Angelka; Tozija, Fimka (IISTE, 2020)
Introduction: In recent years hundreds of thousands of refugees and migrants who have left their homes in order to reach the EU member states have transited through The Republic of North Macedonia (RNM). The dynamics of the refugee crisis in this period continually tested the readiness of the state to fully respect the guarantees of basic human rights, cultural and social differences, as well as respect for human dignity. The R. of North Macedonia throughout the crisis has remained a country of transit, not a target destination for refugees and migrants. The increasing number of migrants makes much more pressure on health systems in countries. Access to health services is one of the most basic issues, because high-quality care and health care is not effective if people don`t have access to it.Purpose of the paper is to represent the right and access to health care for migrants in the Republic of Northern Macedonia, the restriction of the health system, as well as the policies for improving the availability of health services for migrants.Material and Methods: In this paper are used, a public health approach, an infromatic-analytical method and sinteses evidence, and a review of the existing legislation, strategic documents and other documents. The materials whish were used are electronic databases such as PubMed, HINARI, EBSCO, Google Scholar, Scopus, and special search strategies for each keyword database based on inclusion criteria. For a detailed and specific view, were used reports from the International Organization for Migration (IOM)Results and Discussion: With an overall assessment of MIPEX 38/100, the country's policies are barely conducive to social integration. These policies are the result below the European average and an average slightly better than other countries in the region. Migrants lack targeted state support to find the right job, improve their children's education or benefit from consultative bodies. After the adoption of the National Strategy for the Integration of Refugees and Migrants in 2017, as one of the key documents of the Ministry of Labor and Social Policy that regulates the country's policy in dealing with affirmed refugees and foreigners on its territory, in 2018, the Action plan for the integration of refugees and foreigners 2017-2027. Migrants and refugees have multiple barriers to access to health care, as well as discrimination in access to the asylum procedure - which indirectly affects the exercise of healthcare rights.Conclusion: Despite the efforts made to give a quick response to the migration-refugee crisis, the Republic of North Macedonia needs further improvement of the respect and protection of the human rights of migrants and refugees. Health system reforms are needed in order to provide a faster and more efficient response to the needs of vulnerable groups who are staying and transiting through the Republic of North Macedonia.
Keywords: migrants; refugees; health care; health care system; Republic of North Macedonia